Optimizing Friction Losses of Conveyor Systems Using Large-Diameter Idler Rollers - Tiago Cousseau; Jayne O’Shea; Peter Robinson; Shawn Ryan; Stephan Hoette; Yusuf Badat; Michael Carr; Craig Wheeler (Lubricants)
This study investigates the influence of idler roller diameter on indentation rolling resistance and idler rotating resistance in belt conveying systems, crucial for long-distance bulk material transport. It encompasses the impact on grease-lubricated rolling bearings, grease-filled labyrinth seals, and lip seals, with the aim of optimizing energy consumption. Experimental devices were used to refine predictive models, demonstrating that larger idler rollers reduce both resistances, leading to a 40% to 55% efficiency improvement. The study offers a detailed breakdown of friction losses under various operating conditions and provides valuable insights for lubricant selection and system enhancement, highlighting the significance of idler roller diameter in reducing energy costs and enhancing system performance.